PENGARUH PEMBERIAN REBUSAN DAUN SELEDRI (Apium Graveolens L) TERHADAP TEKANAN DARAH PADA WANITA MENOPAUSE DENGAN HIPERTENSI - Diah Evawanna Anuhgera; Rizky Yolanda; Riris Sitorus; Nikmah Jalilah Ritonga; Damayanti . (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
Woman menopause in hypertension is often associated with increase vascularity and physiological changes during menopause. This study aims to examine the effect of celery leaf stew on blood pressure levels in menopausal woman in hypertension. This study was a quasy experiment with pretest-posttest control group design, conducted in the Sidodadi Village District Beringin, Deli Serdang on Januari to March 2020. There were 28 participants selected using purposive sampling, with 14 assigned in the experimental and control group. Data were analyzed using paired t-test and unpaired t-test. There were statistically significance difference of blood pressure levels before and after intervention in the experiment group with p value sitolic level 0.000 dan diastolic level 0.001 (<0.05). Celery leaf stew has a significant effect in reducing blood pressure level in menopausal woman in hypertension. This intervention could be applied as an alternative theraphy in treating menopausal woman in hypertension.